Six Sinopoda species (Araneae: Sparassidae) from Fujian and Yunnan Provinces in China - Zhong, Yang; Cao, Xiaowei; Liu, Jie (Zootaxa, 2017)
Five new Sinopoda species collected from China are diagnosed, described and illustrated: S. afflata sp. nov. (♀, Yunnan), S. horizontalis sp. nov. (♀, Fujian), S. liui sp. nov. (♀, Fujian), S. mamillata sp. nov. (♂♀, Yunnan), S. separata sp. nov. (♀, Yunnan). The female of S. anguina Liu, Li & Jäger, 2008 is described for the first time from Nujiang Lisu Autonomous Prefecture and Baoshan City, Yunnan province, China.